Environmental Nanotechnology, Applications and Impacts of Nanomaterials, Second Edition - Wiesner, Mark; Bottero, Jean-Yves (McGraw-Hill Education, 2016)
Cowritten by leaders of two of the most prominent research groups in the world considering the effects of nanomaterials on the environment, this timely, advanced resource features 75% new material and offers comprehensive coverage of the impacts of nanomaterials on organisms and ecosystems and their applications within industry.